Influence of the orientation and the angle of inclination in the metal roof - Alcívar, Miguel Angel Alban; Ramos, Jorge Lider Macias; Velez, Danny Emir Alcivar (Linguistics and Culture Review, 2022)
Postmodern architecture is responsible for carrying out the building distributions of the urban canyon of cities; For this, it provides the tools required to adjust the territory to social, economic, and environmental needs. One of these tools is aimed at the applicability of construction strategies such as the correct solar orientation. The present investigation of an experimental nature, carried out in the Crucita parish of Ecuador, evaluates the thermal temperatures inside two houses in their current state, assessing it in two prototypes with one water and two waters on the four cardinal orientations: with four different angles of inclination of the cover. Where it was determined that the thermal comfort inside that provides the least increase in temperature is for the house with a roof facing west, with an angle of inclination greater than 20°.